2020
DOI: 10.1177/0379572120912161
|View full text |Cite
|
Sign up to set email alerts
|

Maya K’iche’ Food Groups and Implications for Guatemalan Food Guidelines

Abstract: The anthropology of linguistics, food, and nutrition sciences has a key role with regard to taking a critical look at the Guatemalan Food Guidelines (GFG). These GFG are communicated to native communities to interpret their eating patterns and the structural cognitive interpretation of these food groups in a cultural context. Our understanding of food is informed by cognitive structure represented by language. Since food is fundamental in human cultural identities, understanding food and food categories from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Adequate nutrition is the outcome of a complex collection of factors: cultural and personal preferences, food security, employment, gender, and social views (Kadetz, 2014). In Guatemala, adequate nutrition is compounded by multiple indigenous groups, numerous dialects, and people living in remote conditions (Cuj et al, 2020; Kadetz, 2014). Brown et al (2016) found Guatemalan mothers acknowledged malnutrition but underestimated its severity.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Adequate nutrition is the outcome of a complex collection of factors: cultural and personal preferences, food security, employment, gender, and social views (Kadetz, 2014). In Guatemala, adequate nutrition is compounded by multiple indigenous groups, numerous dialects, and people living in remote conditions (Cuj et al, 2020; Kadetz, 2014). Brown et al (2016) found Guatemalan mothers acknowledged malnutrition but underestimated its severity.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…In future studies, it would be appropriate to use a more complete household food consumption questionnaire (considering micro and macronutrients) created with the help of locals with an intimate knowledge of the assessed population’s consumption habits. In fact, due to the large number of indigenous Maya participants, it would be necessary for future studies to consider how this population particularly perceive and classify food groups, since culture also affects food knowledge and consumption ( Cuj et al, 2020 ). Another point to take into account in the case of the food intake questionnaire is that it only considers food intake in the previous week, so the information provided in this regard is quite limited.…”
Section: Limitations and Future Studiesmentioning
confidence: 99%